Comparative genome analysis of 52 fish species suggests differential associations of repetitive elements with their living aquatic environments - Zihao Yuan (BMC Genomics, 2018)
Abstract Background Repetitive elements make up significant proportions of genomes. However, their roles in evolution remain largely unknown. To provide insights into the roles of repetitive elements in fish genomes, we conducted a comparative analysis of repetitive elements of 52 fish species in 22 orders in relation to their living aquatic environments. Results The proportions of repetitive elements in various genomes were found to be positively correlated with genome sizes, with a few exceptions. More importantly, there appeared to be specific enrichment between some repetitive element categories with species habitat. Specifically, class II transposons appear to be more abundant in freshwater bony fish than in marine bony fish when phylogenetic relationship is not considered. In contrast, marine bony fish harbor more tandem repeats than freshwater species. In addition, class I transposons appear to be more abundant in primitive species such as cartilaginous fish and lamprey than in bony fish. Conclusions The enriched association of specific categories of repetitive elements with fish habitats suggests the importance of repetitive elements in genome evolution and their potential roles in fish adaptation to their living environments. However, due to the restriction of the limited sequenced species, further analysis needs to be done to alleviate the phylogenetic biases.